Pengaruh Penempatan Kerja dan Dukungan Organisasi terhadap Kinerja dengan Kepuasan Kerja Sebagai Variabel Mediasi Pada Pegawai Pemerintah Non Pegawai Negeri (PPNPN) Kementerian Koperasi dan Usaha Kecil dan Menengah - Nurahmanu Bagus Fajar Raditya; I Ketut R. Sudiarditha; Henry Eryanto (JURNAL MANAJEMEN AGRIBISNIS, 2022)
This study aims to determine the effect of the variable work placement, organizational support, on employee performance with job satisfaction as a mediating variable on the performance of government employees, non civil servants, cooperatives and small and medium enterprises. The sample of this study was 129 respondents using the sampling data used in this study using a Likert scale questionnaire and then analyzed by Structural Equation Modeling (SEM) through the AMOS version 22 program. SEM was used with the aim of confirming using confirmatory factor (CFA). The results in the analysis prove that work placement has an effect on employee performance of 3,851> 1.96, Organizational Support on employee performance of 3,962> 1.96, work goals on employee performance of 5,320> 1.96. As well as the significant influence of Work Placement on Employee Performance through work as a mediating variable, and the influence of Organizational Communication on variables that affect employee performance as a significant influence.